2019
DOI: 10.1021/acsaelm.9b00532
|View full text |Cite
|
Sign up to set email alerts
|

Design Rules for Memories Based on Graphene Ferroelectric Field-Effect Transistors

Abstract: Despite the great progress of ferroelectric gated field-effect transistors (Fe-FETs) based on graphene and other 2D materials, a device model that accurately describes the hysteretic transfer characteristics and provides guidelines on performance enhancement of the Fe-FET is still lacking. Here, we present an experimentally validated analytical model that couples charge displacement of the ferroelectric layer with the charge transport in the graphene layer. The model describes hysteretic transfer characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…An efficient gating of graphene can be strategically coupled with a large polarization field at a ferroelectric interface to build high-performance ferroelectric graphene FET (Fe-GFET) memory devices. The majority of reported Fe-GFETs incorporated a separate ferroelectric layer, while other studies suggested a graphene–ferroelectric composite channel . For flexible memory applications, the prototypical ferroelectric copolymer poly­(vinyl fluoride)–trifluoroethylene (PVDF-TrFE) has been widely utilized.…”
Section: Progress Report: a Focus On Structural Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficient gating of graphene can be strategically coupled with a large polarization field at a ferroelectric interface to build high-performance ferroelectric graphene FET (Fe-GFET) memory devices. The majority of reported Fe-GFETs incorporated a separate ferroelectric layer, while other studies suggested a graphene–ferroelectric composite channel . For flexible memory applications, the prototypical ferroelectric copolymer poly­(vinyl fluoride)–trifluoroethylene (PVDF-TrFE) has been widely utilized.…”
Section: Progress Report: a Focus On Structural Classificationmentioning
confidence: 99%
“…There are several important considerations for flexible Fe-GFET memories. For instance, Hassanpour Amiri et al recently proposed modeling-based design rules for Fe-GFETs . This analytical model effectively combined charge displacement of the ferroelectric layer and charge transport in the graphene channel, in the theoretical prediction of an overall hysteretic behavior.…”
Section: Progress Report: a Focus On Structural Classificationmentioning
confidence: 99%
“…An analytical model was previously developed that coupled voltage-dependent charge displacement of the ferroelectric gate layer with the charge transport across the graphene channel. [57] To extend the formalism to multi-bit graphene Fe-FET, the geometrical topography was incorporated in the charge displacement description of the ferroelectric gate layer. The displacement, D, of a ferroelectric gate layer with a constant thickness, t, is the sum of the linear dielectric response and the ferroelectric polarization and is given by…”
Section: Multi-bit Graphene Memory Through Designmentioning
confidence: 99%
“…Pyroelectric energy harvesting (PyEH) is preferred to be operated at lower possible temperatures. Thus, by increasing the temperature of a pyroelectric material, the domains get aligned and give rise to additional electricity by accumulating charges on the top and bottom electrodes. …”
Section: Introductionmentioning
confidence: 99%